Effects of different sleeping positions on intraocular pressure in secondary open-angle glaucoma and glaucoma suspect patients - Sedgewick JH (Dove Medical Press, 2018)
Jeffrey H Sedgewick,1 Justin A Sedgewick,2 Brandon A Sedgewick,2 Berk Ekmekci3 1Private Practice, Ashburn, Virginia, 2Department of Psychology, University of Virginia, 3Department of Statistics, University of Virginia, Charlottesville, VA, USA Purpose: The aim of this study was to investigate the effects of different recumbent sleeping positions of the head and body on intraocular pressure (IOP) in secondary open-angle glaucoma and glaucoma suspect patients, specifically pigmentary dispersion (PD) as measured using the ICare rebound tonometer. Patients and methods: A total of 44 eyes of 24 patients with PD were selected in this study. The IOP of 44 eyes was measured in the initial seated position, in the 4 recumbent positions, and again in the sitting position between each of the recumbent positions. Results: The IOP of the right eyes and left eyes was higher in each of the 4 recumbent positions compared to its initial sitting position (all P<0.001). Dependent (D) vs nondependent (ND) comparisons failed to show a significant difference. All lateral vs prone comparisons showed a higher average IOP in the prone position than in the lateral position regardless of D vs ND status. The range of recumbent IOP changes was -4 to +17 mmHg or -17% to +142%. A total of 64% had at least a ≥33% IOP increase with 43% having a ≥50% increase. Conclusion: Lateral and prone sleeping positions usually do result in significant elevations of IOP in PD patients. Dependency status did not make a difference. A significantly larger IOP increase was seen in the prone position than in the lateral position. The presence of 3 clinical variables (disk hemorrhage [DH], notches, and BV changes) might increase the chances of developing a large recumbent increase in IOP. These patients and possibly all PD syndrome (PDS) or PD glaucoma (PDG) patients should consider sleeping in a bed that allows a head elevation of 30°. Keywords: recumbent position intraocular pressure changes, secondary open angle glaucoma, pigmentary dispersion, intraocular pressure, recumbent intraocular pressure changes